If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + 3z = 56 Combine like terms: 5z + 3z = 8z 8z = 56 Solving 8z = 56 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '8'. z = 7 Simplifying z = 7
| 6r^2+28r=-16 | | 14.00*1.00x=105 | | 8g-3=25 | | 5(4x-7)-(3x-1)2= | | i=400*.12*2 | | 6n^2+22n=8 | | p=2*28+2*70 | | .1x-2.5+2=50 | | f+30=72 | | 8x^2+72= | | 3(m+3)=33 | | 7n^2+45n=28 | | 5a(a+3)-a=-(4a-6)+1 | | 4=8y+5x | | 3x^2+8=-25x | | 10=-2(x-2)+6(x+1) | | 3.5x+7=7 | | 18-7y=-11 | | 2x^2+17x+8= | | -5(4b+2)+(21b-3)=0 | | 2x+x+2x+x=750 | | 20.3=t-(-3.9) | | 3(2t+5)+20= | | 5a(a+3)-a=4a-6+1 | | 40m^2-224=248m | | x+17+x+19-x=602 | | 15x-9x+5=20 | | 5.4-3.7-4.6=0.2-3.1 | | 3(y-4)+6(y+1)=57 | | (m+340)8=4256 | | 2x=15x^2 | | -4r-2(3r-8)=3r+1 |